2021
DOI: 10.3390/ijerph18105466
|View full text |Cite
|
Sign up to set email alerts
|

How Does Metro Maintenance Staff’s Risk Perception Influence Safety Citizenship Behavior—The Mediating Role of Safety Attitude

Abstract: The accident rate is high in subway maintenance work, and most of the accidents are caused by human factors, especially the lack of sensitivity to risk perception, the lack of rigorous attitude towards safety and the lack of safe citizenship behavior (SCB). Therefore, it is very important to study the risk perception (RP), safety attitude (SA) and SCB of metro maintenance staff in order to reduce the accident rate. In order to reduce human errors and accidents, this study analyzed the influence of metro mainte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Moreover, the measurement of PP, RTC, and SCB are currently at an embryonic stage for assessment in the Pakistani healthcare sector. These scales are validated and widely used by numerous studies conducted in other cultures (20,25,59,81,(92)(93)(94)(95)(96). Thus, this study is one of the very few to report these measures in the healthcare sector of Pakistan.…”
Section: Measurement Scalesmentioning
confidence: 99%
“…Moreover, the measurement of PP, RTC, and SCB are currently at an embryonic stage for assessment in the Pakistani healthcare sector. These scales are validated and widely used by numerous studies conducted in other cultures (20,25,59,81,(92)(93)(94)(95)(96). Thus, this study is one of the very few to report these measures in the healthcare sector of Pakistan.…”
Section: Measurement Scalesmentioning
confidence: 99%
“…Many studies have focused on transportation accidents and analyzing the causes of the accident ( Wang et al, 2014 ; Fan et al, 2015 ; Garcia-Herrero et al, 2021 ; Zhai et al, 2021 ). Most results showed that more than 80% of accidents are caused by driver’s operation error, and 90% of accidents are related to the driver’s response to stress conditions, which is influenced by a driver’s anxiety, depression, and other psychological diseases.…”
Section: Introductionmentioning
confidence: 99%